(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Stroke or cerebrovascular accidents ranks first in frequency and emergency among all neurological disorders. Incidence of stroke is coming down in western countries while it is showing an alarming rise in India. Raised homocysteine and serum cholesterol is associated with atherosclerotic vascular events. Aims and Objective: Present study was carried out to find association between high plasma homocystine and total serum cholesterol levels with acute ischemic stroke. Materials and Methods: Study included 30 diagnosed cases of acute ischemic stroke (20 Male and 10 Females) and 30 controls (20 Male and 10 Females) of same age and sex. Blood sample of cases and controls was collected for plasma homocystine and total serum cholesterol levels from venous blood to study the association. Statistical analysis: Data analysis was done using Chi-square test. The outcome of analysis was presented as Chi-square score, df and p value to find out association. The ‘p’ value of less than 0.05 (*p<0.05) was considered as significant. Results: There was significantly higher level of plasma homocysteine and total serum cholesterol in studied stroke patients than controls. Conclusion: There is significant association between plasma homocysteine and total serum cholesterol and acute ischemic stroke. Hence higher levels of plasma homocysteine and total serum cholesterol may be the risk factor for acute ischemic stroke. Further studies on large population are needed to find whether increased level of these parameters can be used as screening test for ischemic stroke.